Distribution and Concentration of Heavy Metals and Polyaromatic Hydrocarbons in Surface Sediments of Kuala Sepetang, Perak, Malaysia - Ismail, Roslan (2007)
A study was condt1cted to determine the concentration and levels of six heavy metals (Ni, Zn, Pb, Cu, Cr and Cd: total 65 samples) and polyaromatic hydrocarbons (PAHs) (16 USEP A listed PAHs: total 45 samples) in the sediment surface layer (0-10 cm) of Kuala Sepetang estuary. Sediment samples were freeze dried (-30°C for 12- 16 hour) to preserve the sample prior to analysis. From the analysis, the sediment pH (range: pH 3.48-7.48), the total carbon (organic and inorganic sources) ranges 1.8-8.3%, higher than the organic carbon (sedimentation and decomposition of leaf litter) content that ranges from 1.3% to 4.2%. The highest CEC was found at Sg. Reba (51.04 cmolc/kg) while other rivers averaged at 20 cmolc/kg. X-ray diffractometry analysis showed dominant presence of kaolinite (7.26A, 3.57 A) and quartz (4.26 A, 3.33 A) in the sediment. On the other hand, sequential extraction showed that Ni, Zn, Pb, Cu, Cr and Cd were primarily present in the residual fraction (non-mobile); especially Ni, Pb and Cd up to 80%. Meanwhile, the heavy metals concentration at S1, S2, S3, S4, S5 and S6 in Kuala Sepetang showed Ni (5 .2-36 mg/kg), Zn (52.4-312.80 mg/kg), Pb (1.8-159.60 mg/kg), Cu (7.6-31.20 mg/kg), Cr (3.2-77.2 mg/kg) and Cd (0.32-5.04 mg/kg) in dry weight basis are comparable with other Malaysian studies. The enrichment factor (EF) value showed very high enrichment of Pb and Cd compared to the other heavy metals. Despite that, Ni, Zn, Cu and Cr concentrations showed deficiency to minimal enrichment, indicating lithigenous material origin rather than anthropogenic input. Meanwhile, total PAHs range from 72ng/g to 2606 ng/g dry weight of sediment. PAHs concentration decreases in the order of: Sg. Reba (S1) (8548 ng/g) > Sg. Selinsing (S4) (5462 ng/g) > Sg. Sepetang (S3) (4249 ng/g) > Sg. Sangga Besar (S5)(32 1 6 ng/g) > Sg. Sepetang (S2) (2961ng/g) > Sg. Sangga Kecil (S6) (1184 ng/g). The concentrations of P AHs reported in Kuala Sepetang were comparable to those reported by Malaysia (Zakaria et al., 2(02) and other regional studies. Generally, Kuala Sepetang showed much lower concentration of total P AHs with mixed pattern of strong pyrolitic and low petrogenic sources compared to Pearl River Estaury, China (408- 10811 ng/g) with high petrogenic origin contamination level. Sediment in Sg. Reba (close to town area) has the most significant correlation (at p<0.01) with physico-chemical properties. This study can be used by environmental agencies and private sector as a baseline data for mangrove sediments.